Investigation of wind power density distribution using Rayleigh probability density function. (January 2019) - Paraschiv, Lizica-Simona; Paraschiv, Spiru; Ion, Ion V.
Abstract: When modelling the wind speed in a given location, the probability distributions prove to be a useful tool. In this paper, the wind power density in an urban and a suburban location in Constanta county, Romania, have been analyzed during the period January 2017 - December 2017, based on the hourly measured mean wind speed data. In this study, the Rayleigh probability density function was used to calculate the wind power density for each location in order to classify them in terms of wind energy. The Rayleigh distribution function has been derived from the available data and is fitted to the measured probability distribution on yearly basis. The power densities reported for the two stations varied from 295.39 to 194.5 W / m 2 .